Ambivalence in Jakarta Air Pollution News on Official Government Website and CNN: an Ecolinguistics Study - Fadhilah, Nada; Suhandano, NFN (Balai Bahasa Kalimantan Tengah, 2024)
Deteriorating air quality conditions elicited public concern, prompting the Indonesian government to implement a series of legislative measures aimed at mitigating Jakarta's air pollution. Media discourse informed both air pollution policy and the government as the predominant source. This research aims to analyze the representation of ideology in the Jakarta air pollution news corpus. The study employs a descriptive and qualitative methodology, utilizing Stibbe's ecolinguistic model. Data processing is facilitated by AntConc 4.2.4 for mapping ambivalent language forms in concordance. The analysis revealed that Jakarta's air pollution is portrayed in various ways, including activities such as public or private electric transportation, vehicle emission tests, and wearing masks, as solutions to air pollution. The utilization of rain, plants, and technology are also presented as solutions to air pollution. The representation of solutions is evidenced by seventeen data points exhibiting ambivalent aspects similar to Stibbe's model, with nine from CNN and eight from government sources.